2016
DOI: 10.1016/j.jalz.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of tau increase in cerebrospinal fluid of APP transgenic mice suggests downstream effect of BACE1 inhibition

Abstract: Our results demonstrate that BACE1 inhibition not only reduces Aβ generation but also downstream AD pathophysiology. The tight correlation between Aβ aggregation in brain and CSF tau levels renders CSF tau a valuable marker to predict the effectiveness of BACE1 inhibitors in current clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 23 publications
5
48
0
Order By: Relevance
“…Cerebrospinal fluid (CSF) was collected from the cisterna magna according to previously published methods (Schelle et al, 2016). Collected blood was incubated for at least 15 min at room temperature and centrifuged at 2,000 g for 10 min, and separated serum was collected and used for sTrem2 measurements.…”
Section: Csf and Serum Collection And Tissue Harvestingmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) was collected from the cisterna magna according to previously published methods (Schelle et al, 2016). Collected blood was incubated for at least 15 min at room temperature and centrifuged at 2,000 g for 10 min, and separated serum was collected and used for sTrem2 measurements.…”
Section: Csf and Serum Collection And Tissue Harvestingmentioning
confidence: 99%
“…Although these data seem to establish the sequence of events in the development of the human disease, it was not known whether a reduction of Aβ generation by inhibition of BACE‐1 has an effect on tau. Recent studies in old APP23 and middle‐aged APPPS‐1 mice showed elevated CSF tau, and this elevation follows the increased Aβ deposition (Maia et al, ; Schelle et al, ). The elevation of tau in these mice was markedly reduced by treatment with NB‐360 and parallels the treatment effects on deposited Aβ (Schelle et al, ).…”
Section: Effect Of Nb‐360 On Ad‐relevant Pathologies Downstream Of Aβmentioning
confidence: 97%
“…In the vehicle groups, the amount of insoluble Aβ increased 1.5‐fold (3‐month treatment) and approximately fivefold (6‐month treatment). Treatment with NB‐360 significantly reduced the Aβ load compared with the vehicle group for both brain Aβ levels and Aβ immunostaining (Schelle et al, ). The doses applied with the NB‐360‐containing chow were sufficient to keep the Aβ close to the baseline.…”
Section: Effects Of Nb‐360 Treatment On Aβ Pathologymentioning
confidence: 98%
See 2 more Smart Citations